Canadian Digestive Health Foundation Public Impact Series 4: Celiac Disease in Canada. Incidence, Prevalence, and Direct and Indirect Economic Impact - Richard N Fedorak; Connie M Switzer; Ron J Bridges (Canadian Journal of Gastroenterology)
The Canadian Digestive Health Foundation initiated a scientific program to assess the incidence, prevalence, mortality and economic impact of digestive disorders across Canada in 2009. The current article presents the updated findings from the study concerning celiac disease.